Transcriptomics‐based analysis of the causes of sugar receding in Feizixiao litchi (Litchi chinensis Sonn.) pulp - Peng, Junjie; Du, Jingjia; Wuqiang, Ma; Chen, Tiantian; Shui, Xian; Liao, Haizhi; Lin, Xiaokai; Zhou, Kaibing (Frontiers in Plant Science, 2022)
To investigate the causes of the “sugar receding” phenomenon in ‘Feizixiao’ litchi (Litchi chinensis Sonn.) pulp, the main sugar contents and sucrose metabolism-related enzyme activities in pulp were measured in 2020 and 2021, and the RNA of the pulp at 35, 63, and 69 days after anthesis (DAA) in 2020 was extracted for transcriptome sequencing analysis. The differential expression of genes was verified by real-time PCR for both years. The results showed that after 63 DAA, the contents of soluble sugars and sucrose decreased, and the contents of fructose and glucose increased in both years. The dynamic changes in sucrose metabolism-related enzyme activities were similar in both years. After 63 DAA, except for acid invertase (AI) activity in 2021, the activities of other enzymes decreased significantly, and the net activity of sucrose metabolism-related enzymes showed a strong sucrose cleavage activity. There were 18061, 19575, and 985 differentially expressed genes in 35 d vs. 63 d, 35 d vs. 69 d, and 63 d vs. 69 d, respectively. Ninety-one genes of enzymes related to sugar metabolism were screened out, and these enzymes included sucrose synthase (SS), sucrose phosphate synthase (SPS), AI, neutral invertase (NI), hexokinase (HK), glucose 6-phosphate dehydrogenase (G6PD), 6-phosphogluconate dehydrogenase (6PGD), phosphofructokinase (PFK), and pyruvate kinase (PK). In 63 d vs. 69 d, seventy-five percent of sucrose metabolism-related enzyme genes were downregulated, seventy-seven percent of genes in glycolysis (EMP) were upregulated and the PFK genes were significantly upregulated. There was a significant linear correlation between the expression of 15 single genes detected by real-time PCR and the RNA-Seq results (r2020 = 0.9139, r2021 = 0.8912). Therefore, at maturity, the upregulated expression of PFKs enhances PFK activity, promoting the degradation of soluble sugar in pulp through EMP, resulting in decreased soluble sugar and sucrose contents, causing “sugar receding” in the pulp. At the same time, the downregulated expression of sucrose metabolism-related enzyme genes in pulp decreased the activities of these enzymes, but the net activity of these enzymes showed a strong sucrose cleavage activity, thus catalyzing the cleavage of sucrose and partially replenishing the reducing sugar content.